Determination of Lead and Chromium in Aloe Vera Pulp and Aloe Vera-Based Cosmetics by Laser-Induced Breakdown Spectroscopy (LIBS). (1st November 2020) - Rehan, Imran; Khan, Muhammad Zubair; Rehan, Kamran; Sultana, Sabiha; Qasim, Irfan; Ud Din, Salah; Anwar, Hafeez; , Sayyar Muhammad
Abstract: This study focuses on the application of laser-induced breakdown spectroscopy (LIBS) to determine lead and chromium in pristine aloe vera and aloe vera based beauty soaps using the second harmonic (532 nm) of a Q-switched Nd:YAG laser. The optimal experimental conditions were evaluated to improve the sensitivity of the detection system by a parametric dependence study. The atomic transition lines at 405.7 nm and 425.4 nm were used as the analytical lines to determine lead and chromium, respectively. The LIBS system was calibrated for these toxic elements and the samples under analysis included 8.00–15.00 ppm by mass of lead and 5.00–12.00 ppm by mass of chromium, which are far above the safe permissible levels of these elements (i.e., 0.50 ppm for Pb and 1.00 ppm for Cr). The quantitative results were checked before and after normalization with the background and better outcomes were obtained when the spectrum was normalized with the background. The LIBS results were compared to the outcomes of selected samples by a standard analytical method, inductively coupled plasma – optical emission spectroscopy (ICP-OES). Both outcomes were in outstanding conformity implying the reliability of the LIBS measurements. The current study is attractive for the general evaluation of human health and specifically for the analysis of aloe vera based cosmetics.